Kecemasan Matematika dan Pemahaman Matematis - Risma Nurul Auliya (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
The aims of this research are intended to examine the effect of mathematics anxiety toward junior high school students’ mathematical understanding ability. The hypothesis of this research was mathematics anxiety had significant effect toward students’ mathematical understanding ability. The research utilized a survey method. The population in this research were students of grade eight from one junior high school in South Jakarta. As the concern, the sample comprised of 66 students who selected by purposive sampling technique. The instrument comprised Mathematics Anxiety Questionnaire. The items were grouped under four sub-headings of attitudinal, cognitive, somatic, and mathematical knowledge/understanding. Two forms of the questionnaire were designed. One sought information on anxiety when working on mathematics in a class consist of 12 items and the other on anxiety on completing a test on mathematics, consist of 16 items. The data analysis used simple linear regression analysis. The result showed that mathematics anxiety had significant effect toward students’ mathematical understanding ability. Keywords: mathematical understanding ability, anxiety, mathematics